Asynchronous, digital teaching in times of COVID-19: a teaching example from general practice - van der Keylen, Piet; Lippert, Nikoletta; Kunisch, Raphael; Kühlein, Thomas; Roos, Marco (GMS Journal for Medical Education, 2020)
Background: The SARS-CoV-2 pandemic had a strong impact on academic teaching and could change it sustainably. Ad hoc digitization of teaching had to be carried out.
CRIS-Team WoS Importer:2021-01-08

Auswirkungen eines Wahlfachs zur evidenzbasierten klinischen Entscheidungsfindung auf die Kompetenzen und Einstellungen von Medizinstudierenden: Eine Pilotstudie - Lippert, Nikoletta; Frank, Luca; Schnitzius, Kathrin; Stubner, Birgit Maria; Kühlein, Thomas; Roos, Marco; van der Keylen, Piet (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2021)
Background: Evidence-based medicine (EbM) as a teaching subject is increasingly taken into account in the Master Plan 2020. To date, neither theoretical requirements nor practical applications of EbM have been consistently implemented in the clinical curriculum. To fill this gap, a digital and tutor-based EbM course has been developed. The aim is to identify the student characteristics (statistical competence, Need for Cognition (NFC), work and experience patterns (AVEM), diagnostic uncertainty) of the first cohort in order to ensure successful course implementation and to prepare future doctors for their role as mediators of health literacy using EbM methods. Methods: The long-term study started in the summer term 2019 with 10 medical students during their clinical training. The measurements were conducted before (t0) and after course attendance (t1). Socio-demographic variables were taken at t0, the Quick Risk Test, PRU questionnaire, the NFC scale and the AVEM were collected at t0 and t1. Results: Half of the students started their doctoral thesis before attending the course. The first test results of the Quick Risk Test (t0) were between 50 % and 90 % and at t1 between 60 % and 100 %. The students showed high scores on the NFC scale (X¯ = 4.6, SD = 0.52, Δ X¯ t0 - t1 = 0.1) and medium scores on the Perfectionism scale (X¯ = 3.8, SD = 0.51, Δ X¯ t0 - t1 = 0.1), Resignation Tendency (X¯ = 3.8, SD = 1.17, Δ X¯ t0 - t1 = 0.1) and on the scale Aggressive Problem Solving (X¯ = 3.9, SD = 1.06, Δ X¯ t0 - t1 = 0.2). They achieved high levels of Anxiety Due to Diagnostic Uncertainty (X¯ = 4.8, SD = 0.69, Δ X¯ t0 - t1 = 0.4) and on the scale Concern about Poor Outcomes (X¯ = 3.9, SD = 1.54, Δ X¯ t0 - t1 = 0.6). The scale Restraint in Disclosing Uncertainty to Patients was more pronounced than the scale Restraint in Disclosing Errors to Physicians (X¯ = 3.5, SD = 0.93, Δ X¯ t0 - t1 = -0.3 compared to X¯ = 2.3, SD = 1.20, Δ X¯ t0 - t1 = 0.1). Discussion: Statistical competence improved with course attendance, with only one student being able to correctly answer all items at t1. NFC and AVEM were strongly expressed and were not very sensitive to change in the sample. The greatest changes were observed on the scales of concern about poor results and fear of diagnostic uncertainty, both of which decreased with course participation. Conclusion: In the long term, the development of a new measuring instrument to assess EbM competencies instead of the Quick Risk Test is conceivable. The longitudinal design will also enable us to make causal interpretations and to track changes in students’ competence feelings, behaviour and attitudes.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Decision-making; Evidence-based medicine; Health literacy; Physicians’ reaction to uncertainty; Quick Risk Test

How confident are medical students about making clinical decisions relying on the evidence? A cross-sectional questionnaire study - Frank, Luca; Hueber, Susann; van der Keylen, Piet; Roos, Marco (GMS Journal for Medical Education, 2019)
Objective: Giving information and providing advice on diagnostic tests is one of the tasks physicians must carry out personally. To do so, they must evaluate the evidence and integrate their findings into everyday practice. Clinical decisions should be based on evidence. How well current medical education prepares for such evidence-based clinical decision-making is largely unclear. Therefore, it was examined how confident medical students are in clinical decision-making based on evidence using epidemiological data. It was examined whether the decision-making confidence increases the higher the semester. Further questions were whether scientifically active medical students show higher decision-making confidence and whether the representation of figures as pictograms rather than tables positively influences the decision-making confidence. Methods: An online survey of the medical students of the Friedrich-Alex-ander-University Erlangen-Nürnberg was carried out. Respondents were presented with three clinical decision-making situations in random order for evaluation in the form of screening scenarios. In each case, the decision-making confidence also had to be specified. The scenarios contained only epidemiological data on existing screening tests. For each scenario, the numbers were presented as a table or a pictogram in a random fashion. In order to avoid false confidence resulting from preconceived opinions neither the illnesses nor the screening tests were mentioned by name. Results: Answers from 171 students were evaluated. Decision-making confidence in dealing with the numbers does not increase in higher semesters (rPearson =0.018, p=0.41). Scientific work is not associated with a higher decision-making confidence (t(169)=-1.26, p=0.11, d=-0.19). Presentation as a pictogram leads to a higher decision-making confidence compared to tables (Pictogram: M=2.33, SD=1.07, Table with numbers: M=2.64, SD=1.11, t(511)=3.21, p<0.01, d=0.28). Conclusions: Medical students from higher semesters show no higher decision-making confidence compared to medical students from lower semesters. Curricular events and scientific work, such as a doctoral thesis, do not seem to strengthen the required skills sufficiently. If evidence is presented in the form of pictograms, this seems to improve student confidence in decision-making.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Clinical decision-making; Doctoral thesis; Evidence-based medicine; Medical students; Pictogram; Uncertainty

Involvement of catecholaminergic neurons in motor innervation of striated muscle in the mouse esophagus - van der Keylen, Piet; Garreis, Fabian; Steigleder, Ruth; Sommer, Daniel; Neuhuber, Winfried; Wörl, Jürgen (Histochemistry and Cell Biology, 2016)
Enteric co-innervation is a peculiar innervation pattern of striated esophageal musculature. Both anatomical and functional data on enteric co-innervation related to various transmitters have been collected in different species, although its function remains enigmatic. However, it is unclear whether catecholaminergic components are involved in such a co-innervation. Thus, we examined to identify catecholaminergic neuronal elements and clarify their relationship to other innervation components in the esophagus, using immunohistochemistry with antibodies against tyrosine hydroxylase (TH), vesicular acetylcholine transporter (VAChT), choline acetyltransferase (ChAT) and protein gene product 9.5 (PGP 9.5), α-bungarotoxin (α-BT) and PCR with primers for amplification of cDNA encoding TH and dopamine-β-hydroxylase (DBH). TH-positive nerve fibers were abundant throughout the myenteric plexus and localized on about 14% of α-BT-labelled motor endplates differing from VAChT-positive vagal nerve terminals. TH-positive perikarya represented a subpopulation of only about 2.8% of all PGP 9.5-positive myenteric neurons. Analysis of mRNA showed both TH and DBH transcripts in the mouse esophagus. As ChAT-positive neurons in the compact formation of the nucleus ambiguus were negative for TH, the TH-positive nerve varicosities on motor endplates are presumably of enteric origin, although a sympathetic origin cannot be excluded. In the medulla oblongata, the cholinergic ambiguus neurons were densely supplied with TH-positive varicosities. Thus, catecholamines may modulate vagal motor innervation of esophageal-striated muscles not only at the peripheral level via enteric co-innervation but also at the central level via projections to the nucleus ambiguus. As Parkinson's disease, with a loss of central dopaminergic neurons, also affects the enteric nervous system and dysphagia is prevalent in patients with this disease, investigation of intrinsic catecholamines in the esophagus may be worthwhile to understand such a symptom.
EVALuna2:35349

Long-Term Endurance Exercise in Humans Stimulates Cell Fusion of Myoblasts along with Fusogenic Endogenous Retroviral Genes In Vivo - Frese, Sebastian; Rübner, Matthias; Suhr, Frank; Konou, Thierry M.; Tappe, Kim A.; Toigo, Marco; Jung, Hans H.; Henke, Christine; Steigleder, Ruth; Strissel, Pamela; Hübner, Hanna; Beckmann, Matthias; et al. (PLoS ONE, 2015)
Myogenesis is defined as growth, differentiation and repair of muscles where cell fusion of myoblasts to multinucleated myofibers is one major characteristic. Other cell fusion events in humans are found with bone resorbing osteoclasts and placental syncytiotrophoblasts. No unifying gene regulation for natural cell fusions has been found. We analyzed skeletal muscle biopsies of competitive cyclists for muscle-specific attributes and expression of human endogenous retrovirus (ERV) envelope genes due to their involvement in cell fusion of osteoclasts and syncytiotrophoblasts. Comparing muscle biopsies from post- with the pre-competitive seasons a significant 2.25-fold increase of myonuclei/mm fiber, a 2.38-fold decrease of fiber area/nucleus and a 3.1-fold decrease of satellite cells (SCs) occurred. We propose that during the pre-competitive season SC proliferation occurred following with increased cell fusion during the competitive season. Expression of twenty-two envelope genes of muscle biopsies demonstrated a significant increase of putative muscle-cell fusogenic genes Syncytin-1 and Syncytin-3, but also for the non-fusogenic erv3. Immunohistochemistry analyses showed that Syncytin-1 mainly localized to the sarcolemma of myofibers positive for myosin heavy-chain isotypes. Cellular receptors SLC1A4 and SLC1A5 of Syncytin-1 showed significant decrease of expression in post-competitive muscles compared with the pre-competitive season, but only SLC1A4 protein expression localized throughout the myofiber. Erv3 protein was strongly expressed throughout the myofiber, whereas envK1-7 localized to SC nuclei and myonuclei. Syncytin-1 transcription factors, PPAR? and RXR?, showed no protein expression in the myofiber, whereas the pCREB-Ser133 activator of Syncytin-1 was enriched to SC nuclei and myonuclei. Syncytin-1, Syncytin-3, SLC1A4 and PAX7 gene regulations along with MyoD1 and myogenin were verified during proliferating or actively-fusing human primary myoblast cell cultures, resembling muscle biopsies of cyclists. Myoblast treatment with anti-Synycytin-1 abrogated cell fusion in vitro. Our findings support functional roles for ERV envelope proteins, especially Syncytin-1, contributing to cell fusion of myotubes.
EVALuna2:17549

„Mind the gap“ – Verzahnung von Wissenschaft und hausärztlicher Praxis - Linking up Science and Family Practice - van der Keylen, Piet; Maun, Andy; Hoyer, Stefanie; Roos, Marco; Beier, Markus; Voigt-Radloff, Sebastian; Frank, Luca (Zeitschrift für Allgemeinmedizin, 2019)
Linking up science and daily practiceis a hallmark or research in family medicine. There is, however, an alarming gap between science and family practice. Due to their decentralized structures, family practices in particular are at risk of being excluded from the scientific developmental process. Within the prospective, multicenter, cluster-randomized GAP study (well-informed physician-patient communication in back pain), the use of an evidence-based internet portal for back pain consultations in family practice is being investigated. In this consortium project – financed by the innovation fund – an intervention through participatory and iterative procedures (integration of family practices) is developed. The new intervention presents medical evidence as communicable and consultable as possible. This article addresses the challenges of linking up science and family practice from the GAP study’s perspective. Family medicine plays an important role in the network of science and daily practice. On the one side, family practice itself is the object of investigation. On the other side, family practice also generates new research questions from everyday routine. The academic family physician – in a dual function as a scientist and family doctor – seems to be predestined to mind the gap between science and primary medical care.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Forschungsprojekte; Hausarztpraxen; hausärztliche Forschung; Praxisrekrutierung; Rückenschmerz

Neurochemical classification of serotonin-immunoreactive neurons co-innervating motor endplates in the mouse esophagus - Zinsser-Krys, Jillena; Kapitza, Christopher; Böhnke, Lena; van der Keylen, Piet; Neuhuber, Winfried; Wörl, Jürgen (Anatomical Record, 2022)
Serotonin immunoreactivity was previously found in myenteric neurons co-innervating motor endplates in the mouse esophagus striated muscle and an involvement in motility control was suggested. However, it is not known if other neuroactive substances are present in these neurons and to what extent they co-localize. First, vasoactive intestinal peptide (VIP) was established as a bona fide marker for putative inhibitory myenteric neurons by evaluating co-localization with neuronal nitric oxide synthase (nNOS) and neuropeptide Y (NPY). Then, co-localization of serotonin and VIP was tested in co-innervating axons on motor endplates, which were visualized with α-bungarotoxin (α-BT) by multilabel immunofluorescence. Myenteric ganglia were also surveyed for co-localization in neuronal perikarya and varicosities. nNOS, NPY, and VIP were completely co-localized in enteric co-innervating nerve terminals on motor endplates. After co-staining with VIP, we found (a) serotonin (5-HT)-positive nerve endings without VIP (44% of 5-HT-positively innervated endplates), (b) 5-HT- and VIP-positive endings without co-localization (35%), and (c) 5-HT- and VIP-positive endings with co-localization (21%). About one-fifth of nerve terminals on motor endplates containing 5-HT originate from putative inhibitory peptidegic nitrergic neurons. However, the majority represents a different population presumably subserving different functions.
CRIS-Team Scopus Importer:2022-07-22
Keywords: 5-hydroxytryptamine; enteric co-innervation; neuromuscular junction; neuronal nitric oxide synthase; neuropeptide Y; vasoactive intestinal peptide

One year of general practice during the COVID-19 pandemic - presentation and evaluation of digital medical education - van der Keylen, Piet; Zeschick, Nikoletta; Langer, Amelie; Kühlein, Thomas; Roos, Marco (GMS Journal for Medical Education, 2022)
Background and teaching situation: The SARS-CoV-2 pandemic had a substantial didactic impact on medical teaching. In Erlangen, the lecture "General Practice" was offered asynchronously and digitally in an inverted-classroom concept. Contents were available via a learning platform. The lecture was presented using annotated videos, consolidation materials and control questions. A forum encouraged for discussions and feedback and collected in-depth aspects for a case-based video consultation. The aim of this work is to evaluate and critically examine the digital teaching concept during the SARS-CoV-2 pandemic.
CRIS-Team WoS Importer:2022-09-09

Psychological stress of general practitioners in the care of patients with palliative care needs: an exploratory study - Lopez, Verena; van der Keylen, Piet; Kühlein, Thomas; Sebastiao, Maria (BMC Palliative Care, 2024)
Background: In Germany, general practitioners play a pivotal role in palliative care provision. Caring for patients with palliative care needs can be a burden for general practitioners, highlighting the importance of self-care and mental health support. This study aimed to explore the role of palliative care in general practitioners’ daily work, the stressors they experience, their coping mechanisms, and the potential benefits of Advance Care Planning in this context. Methods: An exploratory approach was employed, combining a short quantitative survey with qualitative interviews. The analysis was based on a structuring qualitative content analysis, following a deductive-inductive procedure and integrating the Stress-Strain Model and Lazarus’ Transactional Model of Stress and Coping. We recruited eleven general practitioners to take part in the study. Results: General practitioners viewed palliative care as integral to their practice but faced challenges such as time constraints and perceived expertise gaps. Societal taboos often hindered conversations on the topic of death. Most general practitioners waited for their patients to initiate the topic. Some general practitioners viewed aspects of palliative care as potentially distressing. They used problem-focused (avoiding negative stressors, structuring their daily schedules) and emotion-focused (discussions with colleagues) coping strategies. Still, general practitioners indicated a desire for specific psychological support options. Advance Care Planning, though relatively unfamiliar, was acknowledged as valuable for end-of-life conversations. Conclusions: Palliative care can be associated with negative psychological stress for general practitioners, often coming from external factors. Despite individual coping strategies in place, it is advisable to explore concepts for professional psychological relief. Trial registration: Not registered.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Advance care planning; Burden; Coping mechanism; Emotional; General practitioner; Palliative care; Stress; Stressor

The Acceptance, Usability, and Utility of a Web Portal for Back Pain as Recommended by Primary Care Physicians: Qualitative Interview Study With Patients - Schlett, Christian; Roettele, Nicole; van der Keylen, Piet; Schoepf-Lazzarino, Andrea Christina; Klimmek, Miriam; Koerner, Mirjam; Schnitzius, Kathrin; Voigt-Radloff, Sebastian; Maun, Andy; Sofroniou, Mario; Farin-Glattacker, Erik (JMIR Formative Research, 2022)
Background: An ever-increasing number of patients seek health information via the internet. However, there is an overabundance of differing, often low-quality information available, while a lack of health literacy makes it difficult for patients to understand and assess the quality and trustworthiness of the information at hand. The web portal tala-med was thus conceived as an evidence-based, up-to-date, and trustworthy information resource for lower back pain (LBP), which could be used by primary care physicians (PCPs) and patients during and following consultations for LBP. The current evidence demonstrates that patients with LBP could benefit from web portals. However, the use of such portals by patients remains low, thus limiting their effectiveness. Therefore, it is important to explore the factors that promote or hinder the use of web portals and investigate how patients perceive their usability and utility.
CRIS-Team WoS Importer:2023-05-12

The Information needs of internet users and their requirements for online health information - a scoping review of qualitative and quantitative studies - Wollmann, Katharina; van der Keylen, Piet; Tomandl, Johanna; Meerpohl, Joerg J.; Sofroniou, Mario; Maun, Andy; Voigt-Radloff, Sebastian (Patient Education and Counseling, 2021)
Objective This scoping review has been conducted to summarise the information needs of internet users and their requirements for online health information. Methods We searched MEDLINE, Web of Science and Scopus up to July 2019. Qualitative, quantitative and mixed-method studies were included and a thematic synthesis with category formation and exact description of the items was carried out. Results 118 studies were included. To address all users’ needs mentioned in the included studies, we grouped them into nine main categories: authority, comprehension, currency, evidence-based information, exchange with others, independence, purpose, services, user experience. The evaluation showed that website users wanted qualifications of authors to be cited. Users preferred health information that offered interactive elements and resources for relatives, whilst also providing an opportunity for online contact with others. The ease with which information was accessed and the intelligibility of texts were regarded as being very important to users. Conclusion Given the rapid evolvement and changes of online health information, it is crucial to provide up to date insights and a comprehensive overview of the range of criteria. Practice Implications With the results obtained through this scoping review, the creators of online health information could be assisted in providing user-specific resources.<br
Keywords: Information needs; internet users; online health information; scoping review

The Online Health Information Needs of Family Physicians: Systematic Review of Qualitative and Quantitative Studies - van der Keylen, Piet; Tomandl, Johanna; Wollmann, Katharina; Moehler, Ralph; Sofroniou, Mario; Maun, Andy; Voigt-Radloff, Sebastian; Frank, Luca (Journal of Medical Internet Research, 2020)
Background: Digitalization and the increasing availability of online information have changed the way in which information is searched for and retrieved by the public and by health professionals. The technical developments in the last two decades have transformed the methods of information retrieval. Although systematic evidence exists on the general information needs of specialists, and in particular, family physicians (FPs), there have been no recent systematic reviews to specifically address the needs of FPs and any barriers that may exist to accessing online health information.
CRIS-Team WoS Importer:2021-01-22

Treatment thresholds and minimal clinically important effect sizes of antiosteoporotic medication–Survey among physicians and lay persons in Germany - van der Keylen, Piet; Zeschick, Nikoletta; Schlenz, Anna; Kühlein, Thomas (PLoS ONE, 2022)
Background Patient decisions to take preventative treatments for osteoporosis depend on their perceptions of fracture risk, medication effect sizes (ES) of benefits and harms. However, physicians and lay persons may have differing perceptions of risks and medication efficacy. Both tend to overestimate medication benefits. This study surveyed at what risk physicians would prescribe and lay persons would be willing to take bisphosphonates, the minimum ES both groups do demand and the physicians estimates of the actual benefit of bisphosphonates. Design Cross-sectional online questionnaire survey. Methods Respondents were confronted with a case vignette with an osteoporotic patient (10-year femoral fracture risk: 32%). They were asked at what threshold of 10-year-risk of femoral neck fracture they would prescribe or take a drug. They were asked for the minimum ES (absolute risk reduction, ARR) they demand from bisphosphonates to prescribe or take them. Physicians were asked to provide their estimate of the actual ARR of bisphosphonates. Results 114 physicians and 140 lay persons answered (convenience sample/snowball distribution). The 10-year-risk threshold of lay persons (Mdnlay = 60%) willing to take medication was twice as high as the physicians’ threshold (Mdnphy = 30%) to prescribe it (p < .001). The median minimum ARR physicians demanded for bisphosphonates prescription was 17%, whereas lay persons demanded 22% (p < .001). Physicians estimated the actual ARR of bisphosphonates to be 12%. This estimated effect size was below their own minimum threshold for prescription. Conclusions Lay persons tolerate a higher fracture risk and demand a larger benefit of antiosteoporotic medication for fracture prevention than physicians. Physicians demand higher minimum benefits than their own estimates which in turn are above the benefit evidence suggests. Physicians should be more familiar with ES of antiosteoporotic drugs concerning patient outcomes and actively advise lay persons before preventive treatment decisions are taken.
CRIS-Team Scopus Importer:2022-09-02

Well informed physician-patient communication in consultations on back pain - study protocol of the cluster randomized GAP trial - Voigt-Radloff, Sebastian; Schoepf, Andrea C.; Boeker, Martin; Frank, Luca; Farin, Erik; Kaier, Klaus; Koerner, Mirjam; Wollmann, Katharina; Lang, Britta; Meerpohl, Joerg J.; Moehler, Ralph; Niebling, Wilhelm; et al. (Bmc Family Practice, 2019)
Background Back pain is one of the most frequent causes of health-related work absence. In Germany, more than 70% of adults suffer from at least one back pain episode per annum. It has strong impact on health care costs and patients' quality of life. Patients increasingly seek health information on the internet. However, judging its trustworthiness is difficult. In addition, physicians who are being confronted with this type of information often experience it to complicate the physician-patient interaction. The GAP trial aims to develop, implement and evaluate an evidence-based, easy-to-understand and trustworthy internet information portal on lower back pain to be used by general practitioners and patients during and after the consultation. Effectiveness of GAP portal use compared to routine consultation on improving communication and informedness of both physicians and patients will be assessed. In addition, effects on health care costs and patients' days of sick leave will be evaluated.MethodsWe will conduct a prospective multi-centre, cluster-randomized parallel group trial including 1500 patients and 150 recruiting general practitioners. The intervention group will have access to the GAP portal. The portal will contain brief guides for patients and physicians on how to improve the consultation as well as information on epidemiology, aetiology, symptoms, benefits and harms of treatment options for acute, sub-acute and chronic lower back pain. The GAP portal will be designed to be user-friendly and present information on back pain tailored for either patients or physicians in form of brief fact sheets, educative videos, info-graphics, animations and glossaries. Physicians and patients will assess their informedness and the physician-patient communication in consultations at baseline and at two time points after the consultations under investigation. Days of sick leave and health care costs related to back pain will be compared between control and intervention group using routine data of company health insurance funds.DiscussionThe GAP-trial intends to improve the communication between physicians and their patients and the informedness of both groups. If proven beneficial, the evidence-based and user-friendly portal will be made accessible for all patients and health professionals in back pain care. Inclusion of further indications might be implemented and evaluated in the long term.Trial registrationGerman Clinical Trials Register DRKS00014279 (registered 27th of April 2018).
CRIS-Team WoS Importer:2019-03-15

Well informed physician-patient communication in consultations on back pain-study protocol of the cluster randomized GAP trial - Voigt-Radloff, Sebastian; Schoepf, Andrea C.; Boeker, Martin; Frank, Luca; Farin, Erik; Kaier, Klaus; Koerner, Mirjam; Wollmann, Katharina; Lang, Britta; Meerpohl, Joerg J.; Moehler, Ralph; Niebling, Wilhelm; et al. (Bmc Family Practice, 2019)
Background: Back pain is one of the most frequent causes of health-related work absence. In Germany, more than 70% of adults suffer from at least one back pain episode per annum. It has strong impact on health care costs and patients' quality of life. Patients increasingly seek health information on the internet. However, judging its trustworthiness is difficult. In addition, physicians who are being confronted with this type of information often experience it to complicate the physician-patient interaction. The GAP trial aims to develop, implement and evaluate an evidence-based, easy-to-understand and trustworthy internet information portal on lower back pain to be used by general practitioners and patients during and after the consultation. Effectiveness of GAP portal use compared to routine consultation on improving communication and informedness of both physicians and patients will be assessed. In addition, effects on health care costs and patients' days of sick leave will be evaluated. Methods: We will conduct a prospective multi-centre, cluster-randomized parallel group trial including 1500 patients and 150 recruiting general practitioners. The intervention group will have access to the GAP portal. The portal will contain brief guides for patients and physicians on how to improve the consultation as well as information on epidemiology, aetiology, symptoms, benefits and harms of treatment options for acute, sub-acute and chronic lower back pain. The GAP portal will be designed to be user-friendly and present information on back pain tailored for either patients or physicians in form of brief fact sheets, educative videos, info-graphics, animations and glossaries. Physicians and patients will assess their informedness and the physician-patient communication in consultations at baseline and at two time points after the consultations under investigation. Days of sick leave and health care costs related to back pain will be compared between control and intervention group using routine data of company health insurance funds. Discussion: The GAP-trial intends to improve the communication between physicians and their patients and the informedness of both groups. If proven beneficial, the evidence-based and user-friendly portal will be made accessible for all patients and health professionals in back pain care. Inclusion of further indications might be implemented and evaluated in the long term. Trial registration: German Clinical Trials Register DRKS00014279 (registered 27th of April 2018).
CRIS-Team Scopus Importer:2019-05-02
Keywords: Evidence-based medicine; Health communication; Internet portal; Lower back pain; Primary health care